Hegemoni Budaya dan Transendensi Syafa'at dalam Al-Hamziyyah Al-Nabawiyyah Karya Ahmad Syauqi: Studi Semiotika Roland Barthes : Cultural Hegemony and the Transcendence of Syafa'at in Ahmad Syauqi's Al-Hamziyyah Al-Nabawiyyah: A Semiotic Study by Roland Barthes - Saputra, Indra; Rokhim, Minatur; Choironi, Merry; Alfarisi, Salman; Zahiyah, Adibah Bahirah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Modern Arabic literature during the Neoclassical period (al-madrasah al-ihya’iyyah) serves not only as a medium of aesthetic expression but also as a strategic cultural response to the socio-political conditions faced by Muslims under the pressure of Western colonial hegemony. Qasidah Al-Hamziyyah Al-Nabawiyyah by Ahmad Syauqi is one of the monumental masterpieces that uniquely combines elements of praise (madih) to the Prophet Muhammad with sharp social criticism (naqd ijtima’i) towards the reality of his time. Unfortunately, academic readings of this work have often been limited to formalistic aspects, such as meter and rhetoric studies, so that the ideological dimensions and content of resistance hidden behind the beauty of its poetic diction have not been comprehensively revealed. This study aims to fill this gap by employing descriptive qualitative methods, drawing on Roland Barthes’ semiotic approach. The analysis focuses on three layers of meaning: denotation, connotation, and myth (signification), with data sourced from the closing verses of Al-Hamziyyah, which contain a transition from praise to complaint (syakwa). This study found that Ahmad Syauqi constructed three main myths as a form of symbolic resistance. First, the myth of the "Delegitimation of Western Modernity," in which the symbol of Ruma (Rome) is used to undermine the narrative of European legal superiority and affirm the justice of Sharia. Second, the myth of the "Sacralization of Art," in which the diction 'ara'is (bride) naturalizes poetry as a sacred tool for spiritual transactions. Third, the myth of "Syafa'at as the Absolute Solution," which places Islamic spirituality above the rationality of materialism as a way out of the ummah's crisis. Through Barthes's approach, it is revealed that Al-Hamziyyah is not merely a religious text, but a counter-hegemonic discourse that affirms the superiority of Islamic spirituality in the face of modern civilization.